2021
DOI: 10.4315/jfp-20-339
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella enterica in Flies on a Diversified Cattle and Fresh Produce Farm across Two Growing Seasons

Abstract: Flies are a vector for spreading foodborne pathogens pertinent to fresh produce, such as Shiga-toxigenic Escherichia coli and Salmonella; however, most studies focus on concentrated animal feeding operations, which do not reflect low-density animal farming practices that often adjoin fruit and vegetable acreage.  In this study, we determined the prevalence of Salmonella in flies collected biweekly on an integrated animal and produce operation over two growing seasons. Eleven pooled samples, out of 889, tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Hamilton et al. (2021) reported the prevalence of Salmonella in different fly families, around a produce plot nearby two low‐density beef cattle operations, as 2.2%–15.2%. Trap location was not a significant predictor for Salmonella prevalence and the prevalence estimations from this study were different from that of Berry et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hamilton et al. (2021) reported the prevalence of Salmonella in different fly families, around a produce plot nearby two low‐density beef cattle operations, as 2.2%–15.2%. Trap location was not a significant predictor for Salmonella prevalence and the prevalence estimations from this study were different from that of Berry et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although a few vaccines were shown to be effective against E. coli O157:H7 colonization of cattle, vaccines have not been used extensively in cattle production and vaccine efficacy has not been demonstrated clearly up to date. Other preharvest strategies include controlling wildlife access to produce fields by lethal and nonlethal methods such as hunting, trapping, and fencing (Jay‐Russell et al., 2012; Karp et al., 2015; Mishra et al., 2017), pest control (Berry et al., 2019; Hamilton et al., 2021), dust control (Yanamala et al., 2011), implementation of vegetative buffer zones (Glaize et al., 2021; Karp et al., 2015), and remediation and treatment of soil surrounding production areas (Glaize et al., 2021; Karp et al., 2015). Among these interventions, only the vegetative buffer zones were tested experimentally and reported as effective (Glaize et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global surveys demonstrated that adult house flies from urban and agricultural settings possess >200 pathogenic bacterial taxa including key species important to human and animal health such as Salmonella spp. [ 14 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], pathogenic strains of E. coli [ 22 , 47 , 48 , 49 , 50 , 51 , 52 ], Campylobacter spp. [ 49 , 50 , 53 , 54 , 55 , 56 ], Aeromonas cavie [ 57 ], and bacterial pathogens causing bovine respiratory disease Mannheimia haemolytica , Pasteurella multocida , Histophilus somni [ 58 ].…”
Section: Wild House Flies Are Potential Threats To Animal and Human H...mentioning
confidence: 99%